Wheezes and desert breezes: when asthma and valley fever collide*. (7th February 2016) - Azadeh, Natalya; Rank, Matthew A.; Lewis, John C.; Wesselius, Lewis J.; Cheng, Meng-Ru; Blair, Janis E.
Abstract: Objective : To evaluate interactive effects of pulmonary coccidioidomycosis and asthma. Methods : We identified three groups of 33 age- and sex-matched patients: Group 1 (both asthma and coccidioidomycosis), Group 2 (asthma only), and Group 3 (pulmonary coccidioidomycosis only). Predetermined end points included: rate of disseminated coccidioidomycosis, duration of symptoms and antifungal therapy, hospitalization, death, and escalation of asthma therapies. Results : Baseline characteristics were similar across groups. Group 1 patients had worsening asthma outcomes (except forced expiratory volume in 1 s) with coccidioidomycosis. They required more asthma medications (median, 2.0 vs 0.0; p  < 0.001), more corticosteroids (mean [SD], 0.9 [4.2] vs 0.3 [0.6]; p  < 0.001), and more healthcare visits (mean [SD], 0.2 [0.4] vs 0.1 [0.3]; p  = 0.03). Groups 1 and 3 had no differences in coccidioidal end points, including rates of dissemination (1 vs 0; p  > 0.99), symptom duration (mean, 15.2 vs 23.6 weeks; p  = 0.24), antifungal treatment ( n  = 21 [63.6%] vs n  = 24 [72.7%]; p  = 0.60), and treatment duration (median, 26.5 vs 11 weeks; p  = 0.09). Ten patients in Group 1 versus none in Group 3 required systemic corticosteroids for coccidioidomycosis ( p  < 0.001). Conclusions : Active pulmonary coccidioidomycosis significantly worsens asthma outcomes. Asthma (or its treatment) does not worsen coccidioidal outcomes, despite increasing the likelihood of treatment with systemic corticosteroids.